Mitochondrial Traits Previously Associated With Species Maximum Lifespan Do Not Correlate With Longevity Across Populations of the Bivalve Arctica islandica - Rodríguez, Enrique; Dégletagne, Cyril; Hagen, Tory M.; Abele, Doris; Blier, Pierre U. (Frontiers in Physiology, 2019)
The mitochondrial oxidative stress theory of aging posits that membrane susceptibility to peroxidation and the organization of the electron transport system (ETS) linked with reactive oxygen species (ROS) generation are two main drivers of lifespan. While a clear correlation has been established from species comparative studies, the significance of these characteristics as potential modulators of lifespan divergences among populations of individual species is still to be tested. The bivalve Arctica islandica, the longest-lived non-colonial animal with a record lifespan of 507y, possesses a lower mitochondrial peroxidation index (PI) and reduced H2O2 efflux linked to complexes I and III activities than related species. Taking advantage of the wide variation in maximum reported longevities (MRL) among 6 European populations (36 to 507y), we examined whether these two mitochondrial properties could explain differences in longevity. We report no relationship between membrane PI and MRL in populations of A. islandica, as well as a lack of intraspecific relationship between ETS complex activities and MRL. Individuals from brackish sites characterized by wide temperature and salinity windows had, however, markedly lower ETS enzyme activities relative to citrate synthase activity. Our results highlight environment-dependent remodeling of mitochondrial phenotypes.